Prospective Associations Between Diffusion Tensor Imaging Parameters and Frailty in Older Adults. Issue 5 (25th January 2020) - Maltais, Mathieu; de Souto Barreto, Philipe; Perus, Lisa; Mangin, Jean‐François; Grigis, Antoine; Chupin, Marie; Bouyahia, Ali; Gabelle, Audrey; Delrieux, Julien; Rolland, Yves; Vellas, Bruno; ,
Abstract : BACKGROUND: Cross‐sectional associations have been found between frail individuals and worse white matter (WM) integrity. However, the prospective association between WM integrity and frailty is still unclear. Our objectives were to measure associations between WM integrity using diffusion tensor imaging (DTI) and the 5‐year worsening of frailty in community‐dwelling older adults. DESIGN: Secondary analysis of the randomized controlled Multidomain Alzheimer Preventive Trial (MAPT). SETTING: Thirteen memory centers in France and Monaco between 2008 and 2011. PARTICIPANTS: Participants (mean age = 74.7 ± 3.9 years) with no dementia at baseline who had functional magnetic resonance imaging performed as part of the MAPT study (n = 227). MEASUREMENTS: Fractional anisotropy and mean diffusivity (MD), axial diffusivity (AxD), and radial diffusivity (RD) were acquired for 10 different brain regions. Frailty was assessed by the Fried frailty phenotype (score from 0 to 5, higher is worse) at up to seven time points for 5 years. Mixed effect ordinal logistic regression model was used to assess the prospective association between DTI parameters (independent variables) and frailty (dependent variable). All the analyses were adjusted for age, sex, baseline total intracranial volume, and the presence of one of the following cardiovascular risk factors (hypertension, diabetes, and/or hypercholesterolemia). RESULTS: A statistically significant association was found between the RD, AxD, and MD for different brain regions (anterior limb of internal capsule, external capsule, posterior corona radiata, posterior thalamic radiation, superior corona radiata, superior frontal occipital fasciculus, and superior longitudinal fasciculus) and worsening of frailty over 5 years after adjusting for multiple comparisons. CONCLUSIONS: This is the first study to show that WM integrity is associated with frailty in older adults. The mechanisms related to these results require further investigation. J Am Geriatr Soc 68:1050–1055, 2020